The Development of Story Telling Learning Model To Improve Early Childhood Kids’ Empathy Feeling - Darajat Rangkuti; Sukmawarti Sukmawarti (PG PAUD FIP UNIMED, 2017)
One of problems for early childhood kids is optimal growth and development of their empathy. Empathy is social concept which is needed to be introduced for kids because it has important role in social skill development. Empathy feeling cannot suddenly rise inside the kids, it occurs because of imitation and habitual action through environment. The less development of kids’ empathy feeling is caused by ineffective applied learning model for them. The problem formulation of this research was how the effective story telling learning model in order to increase early childhood kids’ empathy is. The goal of this research was to develop the effective story telling learning model in order to increase early childhood kids’ empathy. This research was Borg and Gall research development model, with stage consisted of Define, Develop, Product Experiment and Product Model.The subject of the research was Class B student of PAUD Az-Zaitun Medan. The object of the research was early childhood kids’ empathy. Based on the data analysis, it could be concludes that story telling learning model was significant in improving kids’ empathy. It was suggested for PAUD’s teacher to apply the story telling learning model as one of alternative learning model in improving kids’ empathy feeling.